2010
DOI: 10.1377/hlthaff.2010.0262
|View full text |Cite
|
Sign up to set email alerts
|

Americans’ Conflicting Views About The Public Health System, And How To Shore Up Support

Abstract: This analysis of national opinion polls shows that a majority of Americans support increased spending on public health in general and that they see public health interventions as saving money in the long term. At the same time, many do not favor increased federal spending in a number of areas that public health officials deem important. In addition, polls show striking partisan differences, with Republicans much less supportive than Democrats of additional spending on public health. This split may have politic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…These data also showed that having a greater proportion of Democrats than Republicans in a district predicted stronger policies. This may reflect a predominantly Democratic political belief that government has a role in ensuring health for all, or perhaps a philosophical agreement with the notion of the importance of environment over personal responsibility in improving children's nutrition and physical activity levels 20,21 . Other research on the link between political orientation and school wellness state legislation found that states with Democratic governors and legislatures not controlled by Republicans were more likely to introduce and enact state legislation supporting obesity prevention in schools 22 …”
Section: Discussionmentioning
confidence: 99%
“…These data also showed that having a greater proportion of Democrats than Republicans in a district predicted stronger policies. This may reflect a predominantly Democratic political belief that government has a role in ensuring health for all, or perhaps a philosophical agreement with the notion of the importance of environment over personal responsibility in improving children's nutrition and physical activity levels 20,21 . Other research on the link between political orientation and school wellness state legislation found that states with Democratic governors and legislatures not controlled by Republicans were more likely to introduce and enact state legislation supporting obesity prevention in schools 22 …”
Section: Discussionmentioning
confidence: 99%
“…387 Finally, aside from highly visible catastrophic events, the rationale driving public health action is often based on probabilistic evidence that is in conflict with many people's understanding of what causes ill health or their moral views and values. 388 Americans generally favor the idea of investing in public health prevention; 389 when asked about specific program expenditures, however, support markedly diminishes to a relatively small minority of respondents. 390 Criminal law interventions do not suffer from many of the same "prevention paradox" problems.…”
Section: Crisis As Opportunity: Re-envisioning Us Drug Control mentioning
confidence: 99%
“…In contrast, most Americans believe state health departments are "fair" or "poor" at reducing obesity and promoting healthy lifestyles (54%), improving health for minorities (51%), and preventing chronic disease (54%). 32 A recent poll suggests Americans also attribute health status largely to medical care, individual behavior, microorganisms, stress, and pollution rather than neighborhood, housing, education, employment, and income conditions. Over 75% of a nationally representative sample of 2,423 adults perceived "a great deal" or "quite a bit" of control over their health, with those who perceived less control belonging to groups with lower incomes and less formal education.…”
Section: Health In All Policies and Public Health Preparedness: Cut Fmentioning
confidence: 99%